1V 4.49nW/pixel retinal prosthesis chip with light-to-stimulus duration converter - Choi, Dong Hwi; Jee, Dong Woo (Proceedings - IEEE International Symposium on Circuits and Systems, 2021)
This paper presents 288-pixel retinal prosthesis chip in 0.18 μm CMOS process. Proposed light-to-stimulus duration converter and biphasic stimulator achieve a wide range of retinal stimulation proportional to the incident light intensity at low supply voltages of 1V. The implemented chip demonstrates 18.9x-continuosly-varied stimulus duration control at 6 Hz stimulation rate, and achieves the state-of-the art low power consumption of 4.49 nW/pixel.
Keywords: CMOS processs; Incident light intensity; Low supply voltages; Low-power consumption; Retinal prosthesis; Retinal stimulation; State of the art; Stimulation rates; CMOS sensor; Implantable chip; Light-to-stimulus duration converter; Local return; Low power; Retinal prostheses